A model of firm heterogeneity in factor intensities and international trade. (November 2015) - Emami Namini, Julian; Facchini, Giovanni; López, Ricardo A.
Abstract: Empirical evidence suggests that exporters are, in addition to being more productive, significantly more skilled‐labour intensive than non‐exporters. In a setting that captures both these features, we show that the firm selection induced by trade liberalization works along two dimensions. First, export growth increases competition for skilled labour. This leads to the exit of some of the skilled‐labour intensive firms, while benefitting unskilled‐labour intensive ones. Second, within the group of firms with the same factor intensities, the reallocation of factors is towards the exporters. We show that the increased competition for skilled labour dampens the positive effect of trade liberalization on sector‐wide TFP and real income.